Analisis Pembelajaran Komunikasi Arab dalam Pembelajaran Bahasa Arab di SMA Aisyiyah Boarding School Bandung - Oktaviani, Selpi; Abdurrahman, Maman (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract ÂÂ This research is motivated by the difficulties experienced by students when learning Arabic communication takes place. Therefore, this study aims to describe Arabic communication learning, starting from planning, processing, evaluation and the obstacles that students feel when learning Arabic communication activities. This research uses a qualitative approach with descriptive methods. The sample in this study were students of class x Social and teachers who taught Arabic communication. Data collection techniques used were observation, interviews, documentation and student questionnaires. To analyze the data, researchers used qualitative data analysis with data verification steps, data presentation and data reduction. The results showed that 1) Arabic communication learning planning by the teacher was well prepared, the teacher used the 2013 curriculum and Arabic communication modules that were compiled by themselves 2) The Arabic communication learning process went well and according to the procedure but there were some students who were slow to understand the material provided by the teacher 3) Evaluation of Arabic Communication learning including daily exams, midterm and final semester exams including oral tests, written tests and group assignments. 4) The obstacles experienced by students in learning Arabic communication, namely; the lack of student interest in learning Arabic, the lack of self-confidence when communicating using Arabic, the difference in the student's school background that makes students' Arabic language skills diverse. Keywords: Learning, Speaking, Communication Abstrak Penelitian ini dilatar belakangi oleh adanya kesulitan yang dirasakan siswa ketika pembelajaran komunikasi Arab berlangsung. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan pembelajaraan komunikasi Arab, mulai dari perencanaan, proses, evaluasi serta kendala yang dirasakan siswa ketika kegiatan pembelajaran komunikasi Arab. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Sampel pada penelitian ini adalah siswa kelas x IPS dan Guru yang mengajar komunikasi Arab. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi dan kuisioner siswa. Untuk menganalisis data peneliti menggunakan analisis data kualitatif dengan langkah-langkah verifikasi data, penyajian data dan reduksi data. Hasil penelitian menunjukkan bahwa 1) Perencanaan pembelajaran komunikasi Arab oleh pengajar dipersiapkan dengan baik, guru memakai kurikulum 2013 dan modul komunikasi Arab yang disusun sendiri 2) Proses pembelajaran komunikasi Arab berjalan dengan baik dan sesuai prosedur namun ada bebrapa siswa yang lamban memahami materi yang diberikan guru 3) Evaluasi pembelajaran Komunikasi Arab diantaranya tadalah ujian harian, ujian tengah semester dan ujian akhir semester meliputi test lisan, test tulis dan tugas berkelompok. 4) Kendala yang dialami siswa dalam pembelajaran komunikasi Arab yaitu; kurangya minat siswa dalam mempelajari bahasa Arab, kurangnya rasa percaya diri siswa ketika berkomunikasi menggunakan bahasa Arab, perbedaan latar belakang sekolah siswa yang menjadikan kemampuan berbahasa Arab siswa beragam. Kata Kunci: Pembelajaran, Maharah Kalam, Komunikasi